2010
DOI: 10.1002/anie.201004041
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Aminophosphines as Novel P‐Stereogenic Building Blocks for Ligand Synthesis

Abstract: In this Communication, the enantiomeric excess reported for the hydrogenation of N-(3,4-dihydronaphthalen-2-yl)acetamide was incorrect. An unnoticed impurity contained in the racemic sample led to the use of an inappropriate HPLC method for the determination of the optical purity. Reanalyzing the sample with a correct HPLC method (Chiralcel OD-H, hexanes/isopropyl alcohol (95:5), 1.0 mL min À1 , 210 nm, t(À) = 23.5 min, t(þ) = 27.5 min) [1] showed that the reduction product was obtained in only 9 % ee. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 44 publications
2
68
1
Order By: Relevance
“…Suitable crystals of R‐ 6 for X‐ray analysis were obtained upon layering diethyl ether over a solution of Rh complex in CH 2 Cl 2 (Figure 5). 10 The solid state structure of R ‐ 6 is very similar to that previously reported for complex S ‐ 5 7. The Rh‐coordinated MaxPHOS ligand shows a bite angle of 70.1° and a PNP angle of 101.9°.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Suitable crystals of R‐ 6 for X‐ray analysis were obtained upon layering diethyl ether over a solution of Rh complex in CH 2 Cl 2 (Figure 5). 10 The solid state structure of R ‐ 6 is very similar to that previously reported for complex S ‐ 5 7. The Rh‐coordinated MaxPHOS ligand shows a bite angle of 70.1° and a PNP angle of 101.9°.…”
Section: Resultssupporting
confidence: 68%
“…The stability of the MaxPHOS⋅HBF 4 salt made this compound an ideal precursor for the reliable preparation of Rh(I) complexes. Our initial procedure used [Rh(cod) 2 ]BF 4 as source of metal (Scheme , method A) 7. In these conditions, an equivalent of base (NaHCO 3 ) was required to neutralize the evolving acid, and the resulting NaBF 4 salts had to be selectively precipitated and filtered to isolate pure [Rh( S ‐MaxPHOS)(cod)]BF 4 ( S ‐ 5 ) as an orange crystalline solid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate that, we moved to perform the asymmetric hydrogenation of the homoallylic alcohols 3,w hich are considered minimally functionalized olefins. [29] During the last decade our group has developed several modular P-stereogenic chiral ligands [30] that have proven to be excellent precursors of chiral catalysts.Although our iridium-P, NM axPHOX [31] family of catalysts (6)h ave been successfully applied to the asymmetric hydrogenation of cyclic enamides, [31a] aryl and alkyl imines, [32] and minimally functionalized olefins, [33] including 2-aryl N-allyl phthalimides, [34] we found that in this particular case,u sing 3a as model substrate,[((4S,5S)-Cy 2 -Ubaphox)Ir(COD)]BAr F 4 (7) [35] gave the best results.…”
Section: Angewandte Chemiementioning
confidence: 99%